On cultural typology and peculiarities of religious praxis - Vladimir Yur’evich Lebedev (Религия, церковь, общество, 2013)
The paper examines structural parallelisms between types of socio-cultural patterns and aspects of religious praxis that are integral to the sphere of social practices.